2017
DOI: 10.3389/fnins.2017.00226
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Transferable EEG Decoder for Online Detection of Error Potential in Target Selection

Abstract: Reliable detection of error from electroencephalography (EEG) signals as feedback while performing a discrete target selection task across sessions and subjects has a huge scope in real-time rehabilitative application of Brain-computer Interfacing (BCI). Error Related Potentials (ErrP) are EEG signals which occur when the participant observes an erroneous feedback from the system. ErrP holds significance in such closed-loop system, as BCI is prone to error and we need an effective method of systematic error de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…The classification accuracies for the different calibration schemes were significantly higher than chance level (calculated with a significance level of 5% [ 53 ]). The accuracies above chance level for the between-day and across-participant calibration schemes are in agreement with several other studies that have reported that ErrPs can be detected using these approaches [ 17 , 22 , 30 , 31 , 32 , 33 , 35 , 36 , 54 ]. The classification accuracies obtained for LDA in between-day and across-participant calibration are similar to what has been reported previously, but lower for ANN.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The classification accuracies for the different calibration schemes were significantly higher than chance level (calculated with a significance level of 5% [ 53 ]). The accuracies above chance level for the between-day and across-participant calibration schemes are in agreement with several other studies that have reported that ErrPs can be detected using these approaches [ 17 , 22 , 30 , 31 , 32 , 33 , 35 , 36 , 54 ]. The classification accuracies obtained for LDA in between-day and across-participant calibration are similar to what has been reported previously, but lower for ANN.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it may not be needed to use as many ErrP and NonErrP epochs as were utilized in this study; it has been reported that a steep increase in classification accuracies was observed after ~50–100 ErrPs were used for calibration [ 33 , 36 , 40 ]. The classification accuracies based on within-day calibration are in agreement with findings in several other studies which have reported a detection performance in the range of roughly 70–90% [ 12 , 13 , 15 , 16 , 17 , 22 , 28 , 30 , 32 , 33 , 56 ]; it should be noted that different classification metrics have been reported. This was the case when using either features or the entire epoch as input for the ANN classifier.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the error recognition based on ErrPs of the late time window was better in dynamic stimulation mode. Static and dynamic visual stimuli in ErrPs-based BCI systems have been widely used, e.g., P300-BCIs with ErrPs correction to improve accuracies [9,23], human-robot co-adaptation using ErrPs [16], and implicit cursor control based on ErrPs [15]. This paper studied the difference between the two stimulation modes and the selection of time window, to improve the BCIs' error recognition accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Observation ErrPs are the key point of error recognition in BCI control. They are generated when a person observes an error in the task performed by a second subject (an agent or other human) [8,9]. The observation ErrPs are usually evoked by visual stimulations, which can be roughly divided into static and dynamic ones.…”
Section: Introductionmentioning
confidence: 99%